Interattribute Distances do not Represent the Identity of Real World Faces - Taschereau-Dumouchel, Vincent; Rossion, Bruno; Schyns, Philippe G.; Gosselin, Frédéric (Frontiers in Psychology, 2010)
According to an influential view, based on studies of development and of the face inversion effect, human face recognition relies mainly on the treatment of the distances among internal facial features. However, there is surprisingly little evidence supporting this claim. Here, we first use a sample of 515 face photographs to estimate the face recognition information available in interattribute distances. We demonstrate that previous studies of interattribute distances generated faces that exaggerated by 376% this information compared to real-world faces. When human observers are required to recognize faces solely on the basis of real-world interattribute distances, they perform poorly across a broad range of viewing distances (equivalent to 2 to more than 16 m in the real-world). In contrast, recognition is almost perfect when observers recognize faces on the basis of real-world information other than interattribute distances such as attribute shapes and skin properties. We conclude that facial cues other than interattribute distances such as attribute shapes and skin properties are the dominant information of face recognition mechanisms.